Transformacja ukraińskiego systemu emerytalnego przez pryzmat procesów demograficznych - Petryshyn, Halyna (Przegląd Wschodnioeuropejski, 2025)
Demography is a key factor requiring pension reform both in Ukraine and around the world. For many years, the country has not made radical changes to the pension rules, despite the noticeable increase in the average life expectancy of citizens and the deterioration of the financial situation of the pension fund. The aim of the article is to analyze the transformation of the Ukrainian pension system through the prism of demographic processes. It is the constitutional obligation of the state to provide pension security to citizens through the system of cash benefits, limited only to financial income. Therefore, the security of the pension system and the protection of the interests of the insured – future and current pensioners are among the most important tasks of the government. In Ukraine, as in most countries of the world, spending for this purpose is one of the largest items of public sector expenditure, and unfavorable demographic trends are potentially a source of further increases in the burden of this expenditure on the economy.